Demodex folliculorum infestations in common facial dermatoses: acne vulgaris, rosacea, seborrheic dermatitis, - Ezgi Aktaş Karabay; Aslı Aksu Çerman (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: Demodex mites are found on the skin of many healthy individuals. Demodex mites in high densities are considered to play a pathogenic role. Objective: To investigate the association between Demodex infestation and the three most common facial dermatoses: acne vulgaris, rosacea and seborrheic dermatitis. Methods: This prospective, observational case-control study included 127 patients (43 with acne vulgaris, 43 with rosacea and 41 with seborrheic dermatitis) and 77 healthy controls. The presence of demodicosis was evaluated by standardized skin surface biopsy in both the patient and control groups. Results: In terms of gender and age, no significant difference was found between the patients and controls (p > 0.05). Demodex infestation rates were significantly higher in patients than in controls (p = 0.001). Demodex infestation rates were significantly higher in the rosacea group than acne vulgaris and seborrheic dermatitis groups and controls (p = 0.001; p = 0.024; p = 0.001, respectively). Demodex infestation was found to be significantly higher in the acne vulgaris and seborrheic dermatitis groups than in controls (p = 0.001 and p = 0.001, respectively). No difference was observed between the acne vulgaris and seborrheic dermatitis groups in terms of demodicosis (p = 0.294). Study limitations: Small sample size is a limitation of the study. The lack of an objective scoring system in the diagnosis of Demodex infestation is another limitation. Conclusion: The findings of the present study emphasize that acne vulgaris, rosacea and seborrheic dermatitis are significantly associated with Demodex infestation. Standardized skin surface biopsy is a practical tool in the determination of Demodex infestation.